2013
DOI: 10.1016/j.sbspro.2013.08.699
|View full text |Cite
|
Sign up to set email alerts
|

Design of Living Spaces in Dormitories

Abstract: In this study, the aim is to determine basic features for an ideal dormitory room by finding answers to questions relating to dorm students' friendly relationships with each other, planning dorm rooms, study environments, heating and lighting services, relationship between dorm rooms and WC-bathroom spaces. Among the second grade students studying at Karadeniz Technical University Faculty of Architecture, Department of Architecture, 6 applicants have been -through accidental sampling method -selected for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Previous studies have shown that first year students may experience higher stress than second year students because they have lower social support in their transition to university ( 61 ). The dormitory environment affects the quality of a student’s life ( 62 ), so, this environment must respond to the needs of all age groups ( 63 ) and promote their interpersonal skills to provide a sense of empathy between them ( 64 ). Bankston believed that students will consider their friends’ views and attitudes to be more important than that of their parents, and they tended to receive their accepted support more from their friends for some interests such as music, entertainment and dress codes ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that first year students may experience higher stress than second year students because they have lower social support in their transition to university ( 61 ). The dormitory environment affects the quality of a student’s life ( 62 ), so, this environment must respond to the needs of all age groups ( 63 ) and promote their interpersonal skills to provide a sense of empathy between them ( 64 ). Bankston believed that students will consider their friends’ views and attitudes to be more important than that of their parents, and they tended to receive their accepted support more from their friends for some interests such as music, entertainment and dress codes ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rekreasi dan ruang sosial menyediakan ruang rekreasi diperlukan untuk memberikan dukungan bagi interaksi antar mahasiswa. Hare Kilicaslan (2013) membahas bahwa preferensi sosial orang berbeda-beda dan memiliki dampak yang signifikan, yaitu ruang budaya dimana asrama dapat mengadakan suasana akademik dengan bantuan fasilitas bagi mahasiswa (Kilicaslan, 2013). Ruang servis yang merupakan area servis terdiri atas ruang maintenance, ruang mekanikal dan elektrikal, ruang sampah, dan ruang penyimpanan untuk fasilitas (Kilicaslan, 2013).…”
Section: Asramaunclassified
“…Hare Kilicaslan (2013) membahas bahwa preferensi sosial orang berbeda-beda dan memiliki dampak yang signifikan, yaitu ruang budaya dimana asrama dapat mengadakan suasana akademik dengan bantuan fasilitas bagi mahasiswa (Kilicaslan, 2013). Ruang servis yang merupakan area servis terdiri atas ruang maintenance, ruang mekanikal dan elektrikal, ruang sampah, dan ruang penyimpanan untuk fasilitas (Kilicaslan, 2013). Ruang belajar yaitu ruang untuk belajar biasanya sudah termasuk di dalam kamar masing-masing (Kilicaslan, 2013).…”
Section: Asramaunclassified
See 1 more Smart Citation
“…To improve the living environment of campus residents, efforts have been extensively made. In 2013, Kilicaslan [19] identified five concerned points about dormitory construction, such as physical conditions of dormitory rooms, study environments in dormitories, functionality of wet areas, socialization, and suggestions. Ding, et al [20] emphasized the importance of behavioral changes to dormitory energy conservation, and developed an agent-based model to simulate energy-saving scenarios under different strategies.…”
Section: Introductionmentioning
confidence: 99%